PROBLEMATIKA BENTUK BUMI DALAM PERSPEKTIF FIQH DAN SAINS - Fathurrahman; Irfan (UIN ALAUDDIN MAKASSAR, 2023)
The view that the Earth is flat originated from the ancient civilizations of the world, such as an Ancient Egypt, Babylonia, Mesopotamia, China, and India. And survived until the time of Aristotle. This understanding was re-developed in the 18th century by an Englishman named Samuel Rowbotham who was inspired by Bible verses. In Indonesia, the idea of ​​a flat Earth began to be heavily debated in 2017 when the Flat Earth 101 YouTube page went viral. The issue of the debate over the shape of the Earth also extends to the religious aspect. Most scholars agree that the Earth is spherical and some think that the Earth is flat, but the issue of the shape of the Earth is not a form of aqidah. While, the practice of worship of Muslims is mostly determined using the calculation of the spherical Earth astronomical model. A number of observations of celestial bodies actually empirically prove the Earth is round, but some groups of people do not believe it. Keywords: Spherical Earth, Flat, Astronomy